2012 IEEE International Ultrasonics Symposium 2012
DOI: 10.1109/ultsym.2012.0451
|View full text |Cite
|
Sign up to set email alerts
|

Two dimensional periodic array of reflection centers on electrodes in SAW resonators

Abstract: Periodic arrays of metallic patches on the electrodes of a "Rayleigh-type SAW resonator" are investigated to suppress undesired modes above resonance frequency. Both, the metallization ratio(ηt) and the period( ‫۾‬ ‫ۺ‬ ) of the patches in transversal direction, were varied. Simulations were performed employing the well established 2D P-matrix model. A well-designed periodic array is capable to suppress all transversal modes within the frequency band for = ቂ, ቃ. By evaluation of the overlap integral of the exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Similar to the energy level in a quantum well, we calculate the velocity of the first symmetric mode in a single velocity well with respect to the effective velocity (v m = λ • f m ), where f m is the n th mode frequency and can be computed using a parabolic approximation of the slowness curve [1]. In reality, the number of PVWs is finite so that the perturbation of the first mode velocity increases toward the end of the PVWs.…”
Section: B Optimized Periodic Arrays With Geometry Variationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the energy level in a quantum well, we calculate the velocity of the first symmetric mode in a single velocity well with respect to the effective velocity (v m = λ • f m ), where f m is the n th mode frequency and can be computed using a parabolic approximation of the slowness curve [1]. In reality, the number of PVWs is finite so that the perturbation of the first mode velocity increases toward the end of the PVWs.…”
Section: B Optimized Periodic Arrays With Geometry Variationsmentioning
confidence: 99%
“…When such resonators are used in filter designs without taking any countermeasures, the transversal modes lead to unacceptable passband ripples [2], [3]. In the previous work [1], we have demonstrated that a 2D periodic array with patches on electrodes can successfully get rid of undesired modes within the frequency band of k y = 0, π p T , where p T is the transversal pitch of the periodic array. However, the resonator exhibits strong conductance at frequencies, where the wavelength of the y-components of the transversal modes is comparable to transversal pitch of the patches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation